Description of a new species of the genus Primeuchroeus Linsenmaier, 1968 (Hymenoptera, Chrysididae) from Korea and redescription of P. malayensis (Linsenmaier, 1982) - Kim, Jeong-Kyu (Zootaxa, 2013)
The genus Primeuchroeus Linsenmaier 1968 is known from the Australian, Oriental, and Afrotropical Regions and numbers 32 species (Bohart, 1988; Kimsey & Bohart, 1991). Three chrysidid specimens collected at the same area in Korea in 2011–2012 belong to the genus Primeuchroeus by having simple mesopleuron lacking scrobal sulcus. According to the key (Bohart 1988), these specimens are identified as P. malayensis by having short Rs stub, by presence of transverse frontal carina (TFC), and pale brown tibiae and tarsi. Primeuchroeus malayensis (Linsenmaier, 1982) is known from Malaysia and Indonesia. The original description was based mainly on coloration, and merely provided external features for species-group distinction (i.e. Primeuchroeus siamensis group), instead of morphological description. A comparison between the paratype of P. malayensis and Korean specimens revealing that our specimens belong to a new species described below. This is the first Palaearctic record of the genus Primeuchroeus. The redescription of P. malayaensis based on female paratype is provided. Type specimens of the new species are deposited in the collection of Biodiversity Institute at Hanseo University (BDIH), Kore